Utilising economically beneficial ants - Majer, Jonathan (1986)
The beneficial effects of ants in agriculture and forestry have already been reviewed in Chapter 11. In the following pages I discuss the methods by which ants have been utilized in crops to limit maladies and highlight the strengths and weaknesses of the various approaches. Arising from this review a checklist of points to consider when promoting beneficial is presented so that future ant manipulation attempts can draw on these experiences. This account distinguishes between species that are physically "introduced" into an area from outside and resident species that are "encouraged" to spread their range or utilize an enemy species more effectively. The term "promoted" collectively refers to both methods.